Propagation instabilities of high-intensity laser-produced electron beams - Tatarakis, M; Beg, F; Clark, E; Dangor, A; Edwards, R; Evans, R; Goldsack, T; Ledingham, K; Norreys, P; Sinclair, M; Wei, M; Zepf, M; et al. (2003)
An innovative target design was used to perform the first studies of the propagation of very high current laser-produced electron beams in a regime relevant to the fast ignition scheme. Although it appears that (Weibel) and two-stream instabilities in plasmas where the beam density was close to the background plasma density-use of cone-guided schemes for fast ignition may be able to reduce the propagation distance of the electron beam and reduce the effect of these instabilities.